Femisida sebagai Ancaman Keamanan Non-Tradisional di Indonesia: Perspektif Human Security dan Feminist Security Studies - Nadhifah Amalia (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2026)
Femicide represents the most extreme manifestation of gender-based violence and therefore cannot be understood merely as an ordinary criminal act, but must be situated as a human security concern requiring state attention. This study examines femicide in Indonesia as a non-traditional security threat through the lenses of human security and feminist security studies, focusing on how the state responds through legal frameworks, institutional arrangements, and policy implementation. The study employs a qualitative method with a descriptive-analytical approach based on a critical review of relevant literature. The findings reveal the absence of explicit legal recognition of femicide within Indonesian law, resulting in a persistent gap between normative commitments and practical enforcement. This gap is reflected in fragmented data collection mechanisms and limited institutional capacity among law enforcement agencies. By reframing femicide as a security issue rather than a conventional criminal matter, this study contributes to existing scholarship by extending Indonesian femicide debates into the field of security studies and highlighting the urgency of a more integrated state response in legal enforcement and institutional strengthening.